From Puerto Rico to Port of War: the changes of the Puerto Rican landscape for war purpose, between 1939 until 1945: the changes of the Puerto Rican landscape for war purpose, between 1939 until 1945 - Nieves Rivera, Jorge (2020)
The historiography on World War II in Puerto Rico brings different analyses on political, economic, military, and geographical topics. However, the environmental history analysis of the impact of policies established by the U.S. government on the island during this period has been meager. The implementation of new policies for military security purposes between 1939 and 1945 also brought an alteration of the island natural landscape that impacted large areas of the topography of the Puerto Rican archipelago. Thanks to a new paradigm in environmental historiography, the environmental effects of wars at the global level have been considered and in turn creates the conditions for reflection on the issue in comparing scenarios. That is why this essay aims to add the environmental analysis in a preliminary way to continue the study on this war and its effects. In addition, we tried to expose the historiographic changes that took place in the middle of the twentieth century in the middle of the Second War and under the Cold War in the Puerto Rican academy. But above all, it seeks to continue including the island to contemporary historiographic debates in the Greater Caribbean and Latin America.